2018
DOI: 10.1002/14651858.cd009315.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional labelling for healthier food or non-alcoholic drink purchasing and consumption

Abstract: Background Nutritional labelling is advocated as a means to promote healthier food purchasing and consumption, including lower energy intake. Internationally, many different nutritional labelling schemes have been introduced. There is no consensus on whether such labelling is effective in promoting healthier behaviour. Objectives To assess the impact of nutritional labelling for food and non‐alcoholic drinks on purchasing and consumption of healthier items. Our secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
195
0
4

Year Published

2018
2018
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(217 citation statements)
references
References 126 publications
(447 reference statements)
5
195
0
4
Order By: Relevance
“…Labels indicating low or light versions of products with health harms (e.g., high fat foods and tobacco) suggest the potential for unintended paradoxical effects, including greater appeal and consumption of total calories when foods are labelled ‘low fat’, and perceived lower harm from cigarettes labelled as ‘light’ (Borland et al ., ; Hammond & Parkinson, ; Kozlowski & Pillitteri, ; Kozlowski et al ., ; McCann et al ., ; Wansink & Chandon, ). For example, foods labelled low fat gain a ‘health halo’ which leads consumers to prefer these products and consume more calories than when presented with the same foods without the labels (Crockett et al ., under review; McCann et al ., ). This self‐licensing effect for overconsumption is most pronounced amongst high consumers (Wansink & Chandon, ).…”
Section: Introductionmentioning
confidence: 99%
“…Labels indicating low or light versions of products with health harms (e.g., high fat foods and tobacco) suggest the potential for unintended paradoxical effects, including greater appeal and consumption of total calories when foods are labelled ‘low fat’, and perceived lower harm from cigarettes labelled as ‘light’ (Borland et al ., ; Hammond & Parkinson, ; Kozlowski & Pillitteri, ; Kozlowski et al ., ; McCann et al ., ; Wansink & Chandon, ). For example, foods labelled low fat gain a ‘health halo’ which leads consumers to prefer these products and consume more calories than when presented with the same foods without the labels (Crockett et al ., under review; McCann et al ., ). This self‐licensing effect for overconsumption is most pronounced amongst high consumers (Wansink & Chandon, ).…”
Section: Introductionmentioning
confidence: 99%
“…) and trials to test the effectiveness of nutritional labels (Crockett et al . ). She also described the importance of presenting evidence to policymakers in an appropriate format and the value of skilled knowledge brokers.…”
Section: Achieving Changementioning
confidence: 97%
“…Developing population level interventions largely requires engagement and action by policymakers but researchers have a role in developing the evidence base for these actions and evaluating their effectiveness. Professor Jebb gave examples from her work of modelling studies to examine the likely impacts of a tax on sugarssweetened beverages (Briggs et al 2017;Quirmbach et al 2018) and trials to test the effectiveness of nutritional labels (Crockett et al 2018). She also described the importance of presenting evidence to policymakers in an appropriate format and the value of skilled knowledge brokers.…”
Section: Achieving Changementioning
confidence: 99%
“…Adding nutritional labelling to menus may reduce the calories people consume, evidence published in the Cochrane Library showed 2. A systematic review of several studies to have looked at the impact of nutritional labels on food and non-alcoholic drinks found that adding calorie labels to menus and next to food in restaurants, coffee shops, and cafes can have an effect.…”
Section: Public Healthmentioning
confidence: 99%